As condições de acesso, permanência e escolarização de estudantes da comunidade de Axipicá, no município de Oriximiná/PA. - Matos, Regiane Prata de (Brasil, 2023)
This work aims to analyze the conditions of access and permanence of students from the rural/riverside community of Axipicá-PA for the extension of schooling in the city of Oriximiná∕PA/PA. The investigation was carried out with the collaboration of students, teachers and servants of the municipal school Santa Terezinha, which offers elementary school, located in the community of Axipicá-PA in the interior of the municipality Of Oriximiná∕PA, Microregion of the Middle Trombetas River in the State of Pará. The methodological procedure followed the qualitative research, with bibliographic review and field research. As a data collection instrument, we used semi-structured interviews and participant observation. The field research was carried out on the dates of June 07 to 30, 2018. As a result of the research, we identified that the path to effective access to schooling for students in Axipicá is still a challenge, due to several factors, including the absence of high school located in the rural/riverside community itself and the economic and social conditions that these subjects experience in the field, which complexes the prolongation of studies in the region. Among the most relevant factors were: the location of the community; the absence of electricity for community families; low income and the financial difficulties arising from it; absence of school and classes other than early childhood education and elementary school in the community. As a result of these factors, there are migratory displacements of these students from rural/riverside communities to schools in the city in search of the right to be able to prolong their studies. In addition, the reports of the interviewees indicated that the municipal and state governments, not guaranteeing access to high school education in the community, make the whole process of school transfer from the community to schools in the municipality, search for high school places, cost the route to study or maintain housing for students, become the responsibilities of families alone. Therefore, the process of schooling the subjects of the field is a social demand that still suffers from invisibility and dismay on the part of the State, in view of the precariousness of public education policies and the absence of the implementation of an education policy aimed at the peoples of the field. Given this scenario, the confrontation can be constructed from the strengthening of the political organization of social movements of rural education, the greater financing of programs for families in the field, the greater participation and supervision of the public power that must be present and active in all territories ensuring access to public education, free and quality, at all levels, for all and all those who need it.